Russian Political Identity Profiles: The Role of Moral Foundations, System Justification, and Resistance to Change - A.M. Muminova; A. Titov; A.A. Batkhina; D.S. Grigoryev (Социальная психология и общество, 2022)
Objectives. To extract profiles of Russian political identity in terms of attitude to the conservative agenda, main ideologies, political parties, and institutions among Russians, as well as to identify the connections of these profiles with moral foundations and motivation for system justification and resistance to change. Subsequent analysis showing what is consolidating and what is divisive among the participants, as well as the key dimensions along which this split takes place.Background. A simple analysis of attitudes towards individual politicians and political parties and other subjects of politics does not allow to understand the relatively stable political views of Russians. At the same time, ideological closeness or disagreement is not psychologically accidental, even among those who are poorly versed in politics. There are always some pre-political psychological variables that reflect the predisposition of people to accept certain explicit ideological preferences that are reflected in specific profiles of political identity.Study design. Cross-sectional one-sample correlation design using data from socio-psychological survey. A person-centered approach was applied in the form of latent profile analysis.Participants. There were 224 participants in study 1 and 125 participants in study 2.Measurements. Moral foundations (Graham et al., 2011), attitude toward conservative agenda (Everett, 2013), system justification (Jost, 2015), resistance to change (White et al., 2020), feelings thermometer (Converse et al., 1980).Results. The greatest differences between the profiles of the Russian political identity were observed in the positive attitude toward capitalism, free market, and freedom of speech, as well as toward the president, patriotism, monarchy, military and national security. These differences were related to support for the current Russian political course and the manifestation of loyalty to it. The differences between the profiles were more related to the binding moral foundations, while the idea of fairness was equally important for Russians with any of the profiles found.Conclusions. Authoritarian submission can be considered a key psychological foundation of the Russian political identity. On the other hand, political views are differentiated by the choice between the demand for security (stabil’nost’) or development (i.e., accepting the risks of changes for the future development, or abandoning them in favor of security, stability, predictability of the current political course).